Learning and teaching experience, theory and pratice, in the chil-mother nursery - Antonia do Carmo Soares Campos; Maria Vera Lúcia Moreira Leitão Cardoso; Maria Grasiela Teixeira Barroso (Rev Rene)
This is an exploratory and critical analysis study, conducted with 24 under graduated nursing students of the nursing care process I discipline from the Federal University of Ceará. It focused on the learning activity towards the newborn child in the child-mother nursery. It aims to identify the level of satisfaction of the students from the learning and teaching experience and the difficulties faced. The activities took place in a child-mother nursery of a maternity hospital in Fortaleza-Ceará, between april and june of 2001. Data was collected by participant observation and semi-structured questionnaire. The analysed data produced the following themes: level of satisfaction of theory and practice; difficulties regarding the pratical learning experience. It conducted that there is good interaction among nurse lecturer, student and assistant nurse, as well as an adequate fieldwork. However, it was mentioned unimpaires relation between nurse lecturer and students, which caused gaps in the learning and teaching process.